2002
DOI: 10.1046/j.1365-3059.2002.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease complexes involving plant parasitic nematodes and soilborne pathogens

Abstract: This review discusses the mechanisms underlying synergistic interactions between phytophagous nematodes and soilborne pathogens, and identifies biotic and abiotic factors affecting these interactions. Approaches towards the resolution and management of nematode-pathogen complexes are considered and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
150
0
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(169 citation statements)
references
References 82 publications
2
150
0
17
Order By: Relevance
“…However, yield losses from combinations of pathogens and disease complexes are not well understood. For example, fungal wilt pathogens and nematodes can have synergistic interactions (Back et al 2002).…”
Section: Economic Impacts Of Soilborne Pathogens and Root Diseasesmentioning
confidence: 99%
“…However, yield losses from combinations of pathogens and disease complexes are not well understood. For example, fungal wilt pathogens and nematodes can have synergistic interactions (Back et al 2002).…”
Section: Economic Impacts Of Soilborne Pathogens and Root Diseasesmentioning
confidence: 99%
“…As complex mixtures, EOs may display several biological activities which makes them desirable biopesticides, being able to control not just the targeted pest but also opportunistic species and resistant strains. This is of particular interest in phytoparasitic nematode control since complex disease symptoms are also commonly associated with accompanying pathogenic microbiota (Back et al, 2002;Vicente et al, 2011). Several EOs, such as those of Cinnamomum zeylanicum (Kong et al, 2006); Boswellia carterii, Paeonia moutan, Perilla frutescens, Schizonepeta tenuifolia (Choi et al, 2007a); Thymus vulgaris (Kong et al, 2007); Litsea cubeba, Pimenta dioica, Trachyspermum ammi ; Coriandrum sativum and Liquidambar orientalis (Kim et al, 2008) have revealed strong activities against B. xylophilus.…”
Section: Introductionmentioning
confidence: 99%
“…This disease complex, induced by the interaction between both pathogens, has increasingly become a serious problem in the Saudi green bean fields and greenhouses. Many reports have clearly shown that the damage caused by rootknot nematodes aid in the development of diseases caused by some soil-borne fungi (Al-Hazmi, 1985;Evans & Haydock, 1993;Back et al, 2002) Several environmental and edaphic factors can influence the interaction between these two pathogens. Subsequently, the development and severity of the resulted disease complex (rootknot/charcoal root rot) on green beans and other crops increased (Tu & Cheng, 1971;Siddiqui & Husain, 1991;Nischwitz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%